Improving the pronunciation of English learners through new learning process - Zhujia Yang; Chalermpon Kongjit (International Journal of Evaluation and Research in Education (IJERE), 2022)
In Thailand, the achievement of English learners has been disappointing, despite the constant efforts to develop English education, and there is an urgent need for Thai learners to focus on the pronunciation of English. The research identified Thai English learners’ specific English pronunciation problems. It also designed and facilitated a new self-directed learning process for learners to improve their English pronunciation, which is based on a combination of a community of practice (CoP) and self-directed learning. There were 15 participants selected purposively involved in this study. This study demonstrated how to use new learning process to identify specific problems and shares how to solve problems by practicing among participants so that the objectives can be reached. The new learning process was useful in helping users to improve their English pronunciation to communicate effectively in real life. The new learning process also can be used for other language learners.